Study on The Influence of Direct Ground Liquid CO2 Injection on Soil Chemical Properties in Subsidence Areas under Shallow Buried Geological Conditions - Naifu Cao; Yuntao Liang; Gang Wang (Journal of Chemistry)
In order to reveal the impact of a high concentration of CO2 on the soil in the coal mining subsidence area, the surface above the goaf before CO2 injection is regarded as a subsidence area model. Based on the actual vertical depth of 70∼80 m shallow buried coal seam geological conditions, CO2 diffusion in the goaf is regarded as a short-term high-concentration CO2 leakage model. The surface soil samples before and after 60 tons of direct injection of liquid CO2 in the goaf of Huojitujing in the Daliuta Coal Mine could be collected to conduct the experimental observation. By measuring the changes in the five indicators of soil air-dried and fresh sample including pH, available nitrogen, available potassium, water-soluble salt, and total organic carbon, the changes of pH and mineral content in the soil could be analyzed quantitatively and qualitatively at different time periods before and after CO2 injection. This proves that the injection of CO2 into the goaf has an impact on the chemical properties of the surrounding soil.